ANALISIS PENDAPATAN PETANI KAKAO DI DESA AMOLA KECAMATAN BINUANG KABUPATEN POLEWALI - Kasmiran Kasmiran; Irmayani Irmayani; Muhdiar Muhdiar (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
This researsch was carried out in Amola Village, Binuang Subdistrict, Polewali Mandar District.from july to August 2018. The study aimed to find out the total production and revenue and total opinionns obtinedin the cacao business in Amola Village, Binuang District, Polewali mandar district. Sampling was doe by using a simple random technique where the number of samples will be taken10 percents of the existing populations so that the total are 36respondents. The data using in this study are primary data and secondary data. Acceptance analysis method for fesibility income analysis and impact point. The results of this study indicate the average amounnt of income obtained by the respondents farmers in Amola Village, Binuang District, Polewali Mandar District, the production of Rp 42.906.666 obtained from the total revenue off Rp 1. 544.640.000 minus the total cost of Rp 266.756.500 B/C ratio obtained is 4,79 it s meaning that cacao farming in Amola Village, Binuang District, Polewali Mandar District, is profitable feasible to develop. Thus cocoa farming in Amola Village, Binuang District, Polewali Mandar District needs to pay attention to efforts to improve and develop.